COVID‑19 mitigation by digital contact tracing and contact prevention (app‑based social exposure warnings) - Soldano, Germán J. (2021)
Fil: Soldano, Germán J. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas; Argentina.